The influence of the initial amelioration degree on the agrophysical indices of long-fallow sod-podzolic soils - A. V. Lednev; A. V. Dmitriev; N. A. Pegova; D. A. Popov (Аграрная наука Евро-Северо-Востока, 2018)
The influence of the initial degree of cultivation on the development of modern soil- forming processes in fallow agrosod-podzolic loamy soils of the Udmurt Republic was established by 2015-2017 studies. It has been shown that three-year weed infestation increased the soil structure, which was expressed in a sharp decrease in the silt fraction content (